Authentic Assessment Techniques on Cognitive Aspects in Islamic Religious Education Learning at Elementary School Level - Ghufran Hasyim Achmad; Andi Prastowo (Jurnal Ilmiah Sekolah Dasar, 2022)
The teacher does not correctly and adequately understand the implementation of a valid assessment, so students do not understand the implementation of a valid assessment. This study aims to analyze how authentic assessment techniques on cognitive aspects are used by Islamic religious education teachers in elementary schools. The type of research used is qualitative research with a descriptive approach. This research uses a case study design because the researcher will reveal in-depth or analyze the research problem to obtain more specific results. The subjects in the study were one teacher of Islamic religious education and two students. The data collection used is primary and secondary sources. The primary sources used were observation, interviews, and documentation, while the secondary sources were reputable books and journals that matched the themes discussed. The data analysis using descriptive-analytic is divided into three stages, namely the critical analysis stage, critical interpretation, and concluding. The results of this study are several authentic assessment techniques on cognitive aspects used by Islamic religious education teachers, including written tests, oral tests, and assignments. This assessment technique is used to get a complete picture of student competencies in the realm of knowledge and can be used as a measuring tool for learning success so that assessment has an essential role in education.